Impact of Lamivudine-Based Antiretroviral Treatment on Hepatitis B Viremia in HIV-Coinfected South Africans - Azwidowi Lukhwareni; Maemu Petronella Gededzha; Edina Amponsah-Dacosta; Jason T. Blackard; Rosemary J. Burnett; Selokela Gloria Selabe; Thanda Kyaw; M. Jeffrey Mphahlele (Viruses, 2020)
This prospective study investigated the impact of lamivudine-containing antiretroviral therapy (ART) on HIV-positive patients in South Africa with baseline hepatitis B virus (HBV) infection. Follow-up samples from 56 HBV/HIV co-infected patients, 25 with occult HBV infection (OBI) and 31 with chronic HBV infection (CHB), were available for analysis. HBV viral loads were quantified at 6, 12, 18, and 24 months post-ART initiation by the COBAS TaqMan HBV Test 48 assay, and the HBV polymerase gene was amplified with an in-house nested polymerase chain reaction assay. During 24 months of lamivudine-based ART, 6 of 8 (75%) OBI and 4 of 6 (67%) CHB patients achieved undetectable levels of HBV DNA, while 2 patients had persistent HBV DNA levels ≥ 2 × 105 despite lamivudine-based ART for 24 months. HIV viremia was undetectable in all patients at 12 months, suggesting high adherence to ART. Several lamivudine-associated HBV resistance mutations, including L180M, A181T, M204I, and M204V, were observed. Sequence analysis also revealed a rare genotype G infection. While resource-limited settings may use lamivudine-based ART because of availability and low cost, antivirals with dual therapy against HBV and HIV (e.g., lamivudine and tenofovir) should always be recommended with the regular monitoring of HBV viremia levels.